Progressions of isometric core training - Mendrin, N.; Lynn, S. K.; Griffith-Merritt, H.; Noffal, G. J. (Strength and Conditioning Journal, 2016)
With the growth in popularity of core training, it is important that there is a clear understanding of how to best tailor these exercises to safely meet the needs of different individuals. Extensive research has shown that training the core muscles isometrically, that is without bending the spine, is safe and may help reduce the incidence of back injury. Exercise professionals must have the ability to modify isometric core exercises and alter their difficulty to ensure that they provide a safe and appropriate challenge for individuals of varying fitness levels and training goals. Therefore, this article summarizes the current research that outlines the potential negative consequences of constantly bending or moving through the spine. This provides the rationale for training the core isometrically to avoid replicating these known mechanisms of injury during exercise. Examples of isometric core exercises of varying difficulty are also provided, as well as a model outlining how to implement these progressions to safely meet the needs of any individual in a general fitness population.